Desain Furnitur dengan Prinsip Keselamatan Siswa (Objek Penelitian: SDN Ketawanggede Kota Malang) - Muhamad, Infaroyya Al Karimah.; Sufianto, Heru; Titisari, Ema Yunita (RUAS, 2024)
In Indonesia, the prevalence of injuries in school-age children is quite high, with around 6.5% of incidents occurring in the school environment. According to WHO (2022), fall injuries are one of the leading causes of death globally, highlighting the importance of injury risk management, especially in primary school-aged children (6–12 years).  Children in this age range have cognitive limitations in recognizing dangerous situations, so a safe physical environment at school is essential to support their safety and learning process. This study evaluates the safety of classroom infrastructure at SDN Ketawanggede, Malang. This study uses a descriptive-evaluative qualitative approach and case study methods to identify risk areas. The results of the study showed that the circulation of classrooms, furniture, and other design elements needed improvement. Recommendations include rearranging furniture and installing whiteboards according to ergonomic standards to improve safety and comfort in the learning process.